NATURAL AGEING EFFECTS ON MICROSTRUCTURE AND PROPERTIES OF RAIL FASTENING ELEMENTS SKL-12 - Krzysztof LABISZ; Jarosław KONIECZNY (Scientific Journal of Silesian University of Technology. Series Transport)
Rail transport is presently one of the most supported means of transport in Europe; it existed from the end of the 18th century. However, some issues especially concerning materials and its exploitation are still actual and are a matter of scientific projects or developments. In this paper, analyses concerning the characterisation of used track infrastructure elements in form of sleepers of the popular rail fastening system SKL 12 were performed. Specifically, the main objective of the work was the characteristics of the material microstructure and properties after long-term usage and natural ageing, reaching over a few decades. In this paper was conducted investigations concerning the non-used and used fasteners by reason of classic material research methods. The analysis was carried out based on the results obtained through research using mainly light, scanning electron microscopy (SEM) and transmission electron microscopy (TEM), as well as electron diffraction for the lattice structure determination, EDS chemical microanalysis and Rockwell hardness testing were also carried out in terms of identification of the chemical analysis changes that occurred after long-term application. The main reason was to characterise the long-term usage for the microstructure changes on the surface layer of the used fasteners compared to newly produced material.